Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Sayuran Hidroponik Dikebun Sayur Surabaya - Khusnarida Khusnarida; Iswati Iswati; Siti Aisah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study entitled The Influence of Product Quality and Price of Hydroponic Vegetables in Surabaya Vegetable Gardens aims to determine how product quality and price affect purchasing decisions. This study was conducted in a Surabaya vegetable garden with a sample size of 100 respondents using the Purposive Sample technique. The data collection method used was the questionnaire method with Google Form. As well as the data analysis techniques used validity test, reliability test, classical assumption test, multiple regression with hypothesis test coefficient of determination, t test and f test at a significance level of 5% (0.05). The Adjusted R Square value or coefficient of determination is 0.947, which means that product quality and price are able to explain the purchasing decision variable by 94.7% while the rest is 5.3%. With f count = 879.270 ˃ ftable = 3.090 with a significance level of <,001b which means less than 0.05, this proves that the variables of product quality and price have a positive and significant effect on the decision to purchase hydroponic vegetables in the Surabaya vegetable garden.